2005
DOI: 10.1193/1.2098629
|View full text |Cite
|
Sign up to set email alerts
|

Object-Oriented Image Understanding and Post-Earthquake Damage Assessment for the 2003 Bam, Iran, Earthquake

Abstract: This paper presents a methodology for quantifying the number of buildings that collapsed following the Bam earthquake. The approach is object rather than pixel-oriented, commencing with the inventory of buildings as objects in high-resolution QuickBird satellite imagery captured before the event. The number of collapsed structures is computed based on the unique statistical characteristics of these objects/buildings within the “after” scene. A total of 18,872 structures were identified within Bam, of which the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(24 citation statements)
references
References 3 publications
0
24
0
Order By: Relevance
“…They used a creative shadow-based filter on fine spatial resolution imagery with a watershed segmentation algorithm to detect and map damaged or undamaged buildings. Gusella et al [115] quantified the number of buildings that collapsed following the 2003 Bam earthquake, by first segmenting pre-earthquake Quickbird imagery and then comparing the spectral signature of those objects in the post-earthquake imagery. They report an overall accuracy of 70% for the damage classification.…”
Section: Review Of Obia and Public Health Applicationsmentioning
confidence: 99%
“…They used a creative shadow-based filter on fine spatial resolution imagery with a watershed segmentation algorithm to detect and map damaged or undamaged buildings. Gusella et al [115] quantified the number of buildings that collapsed following the 2003 Bam earthquake, by first segmenting pre-earthquake Quickbird imagery and then comparing the spectral signature of those objects in the post-earthquake imagery. They report an overall accuracy of 70% for the damage classification.…”
Section: Review Of Obia and Public Health Applicationsmentioning
confidence: 99%
“…More quantitative and details of damages are expected from the damage analysts and disaster management practitioners. Researches in response to recent disaster events showed that detailed information derived from very high-resolution satellite images could accommodate their requirements (Chesnel et al 2007;Gusella et al 2005;Saito et al 2004;Vu and Ban, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Object Based Image Analysis (OBIA) was used previously to map forests (Chubey, M.S. et al 2006), natural catastrophes (effects of an earthquake: Gusella, L. et al 2005) and cities as well (Chen, Y. et al 2007). It has been established that under appropriate conditions OBIA could be more accurate than pixel-based methods (Al Khudairy, D.H. et al 2005).…”
Section: Introductionmentioning
confidence: 99%